Analyzing the Impact of Institutional Quality on Foreign Direct Investment in Burkina Faso - Zakaya Ramde (Current Topics on Mathematics and Computer Science Vol. 4, 2021)
The present study aims to evaluate the impact of the quality of institutions in the mobilization of foreign direct investment in Burkina Faso. This study examined the impact of institutional quality on the attraction of foreign direct investment in Burkina Faso over the period 1985-2005. Different analyses on variables allowed use of error correction modelling (VECM). The results reveal a long- term relationship between foreign direct investment (FDI), corruption, external conflicts and socio-economic conditions. It is therefore necessary for the country to take appropriate measures to strengthen the fight against corruption in all sectors of economy and strengthen the independence of justice, all of which will help to build investors’ confidence. Therefore, there is a need to develop appropriate policies such as strengthening judicial governance and improving existing anti-corruption strategies in Burkina Faso. The country must also be involved in the appropriate way of resolution of external conflicts that keep potential investors away, especially in the West African sub region.